Design and analysis of DNA sequence alignment module using Smith-Waterman scoring patterns / Wan Abdul Qayyum Moh Salleh - Moh Salleh, Wan Abdul Qayyum (2013)
This project is to design and analyze the DNA sequence alignment module using Smith-Waterman scoring patterns. The main objective is to create SW pattern in matrix using Excel based equation. The second objective is to construct the module for SW sequence alignment using the matrix pattern. One of the major problems rose from DNA sequence alignment is the speed and accuracy. The computational demand needed to explore for analyze the data faster and accurate in these databases is quickly becoming a great concern. This system will be using Verilog language and optimize it using pattern recognition in order to overcome the accuracy issues. The system optimizes the aligning DNA fragment using Smith-Waterman algorithm with a pattern recognition algorithm. FPGA design, synthesis and simulation are done using the Xilinx ISE software and obtain the RTL schematic as well as the waveform of the module. Synopsys tools are used for analysis the project in ASIC design. VCS for verification the design for further process in ASIC design tools are used. Design Compiler is for resynthesize and remodelling the design with setup constraints. Static timing analysis using Prime Time is for advance timing analysis. Based on the result obtained, the minimum frequency that is suitable for this project is 50 MHz. The average power consumption for normal compile high compile and ultra-compile are 53 uW, 52.8 uW and 49.8 uW. The average Cell area for normal compile high compile and ultra-compile are 18700 um2, 18280 um2 and 9532 um2.